ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWA MEMILIH PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN FAKULTAS PENDIDIKAN TEKNOLOGI DAN KEJURUAN UNIVERSITAS PENDIDIKAN INDONESIA - Mohamad Dani Juniardi, - (2022)
One of the keys to improving the quality of a Nation's Human Resources was education. The quality of education was an aspect who's determine the progress of a Nation. In Indonesia, education was divided into 3 types, such as : formal, non-formal and informal education. One of formal education is college which consists of various major programs. There are various types of universities in Indonesia, one of them is the Indonesian Education University, Building Engineering of Education study program. In making the decision to choose a study program, various factors must be considered. The purpose of this study was to found out factors who's influence and the most impactfull decisions students to choose major Building Engineering of Education, Faculty of Technology and Vocationall Education, University of Education Indonesia. The research method used in this study iwas quantitative approach method with descriptive analysis including percentages. The factors that influence students to choose the Building Engineering of Education program at FPTK UPI come from internal factors and external factors. Aspects of internal factors that influence students consist of motivation and interest, while aspects of factors that influence from external consist of gender, college image and job prospects. Internal factors are the most influencing factors for students who's choosing the Building Engineering of Education study program FPTK UPI.